Characteristics of Corneal Biomechanics in Chinese Preschool Children With Different Refractive Status. Issue 11 (November 2019) - Long, Wen; Zhao, Yiming; Hu, Yin; Li, Zhouyue; Zhang, Xiaoxiao; Zhao, Wenchen; Yang, Xiao; Cui, Dongmei; Trier, Klaus
Abstract : Purpose: To investigate the characteristics of corneal biomechanics in Chinese preschool children with different refractive status. Methods: Study participants were 108 Chinese children (216 eyes) aged 4 to 6 years with a spherical equivalent refraction between −9.00 and +9.00 diopters (D). Cycloplegic refraction was measured using an autorefractor, axial length using an IOL Master (Zeiss, Oberkochen, Germany), and corneal biomechanical metrics and corneal power using an ultra-high-speed camera (Corvis ST; Oculus, Wetzlar, Germany) and Pentacam (Oculus; Menlo Park, CA). Differences in corneal biometry and biomechanical characteristics among myopia, emmetropia, and hyperopia eyes were analyzed by SPSS 17.0. Results: The spherical equivalent refraction was significantly positively correlated with the stiffness parameter at the first applanation (SP-A1, r = 0.22, P < 0.01) and corneal velocity at the second applanation (A2 velocity, r = 0.25, P < 0.001), whereas it was negatively correlated with the peak distance (r = −0.32, P < 0.001) and deformation amplitude ratio (DA ratio, r = −0.34, P < 0.001). In the hyperopia, emmetropia, and myopia groups, the SP-A1 successively decreased (108.70 ± 22.93 vs. 100.50 ± 18.98 vs. 97.97 ± 18.91, P < 0.01), whereas the peak distance progressively increased (4.39 ± 0.32 vs. 4.56 ± 0.30 vs. 4.63 ± 0.34 mm, P < 0.001). In the same order of groups, an increasing trend was found for the axial length (21.11 ± 0.76 vs. 22.39 ± 0.72 vs. 24.09 ± 1.37 mm, P < 0.001), central anterior chamber depth (CACD, 3.04 ± 0.41 vs. 3.21 ± 0.33 vs. 3.37 ± 0.40 mm, P < 0.001) and flat meridian keratometry (K1, 41.92 ± 1.59 vs. 42.73 ± 1.39 vs. 42.98 ± 1.60 D, P < 0.001). Central corneal thickness significantly decreased in the same order of groups (565.46 ± 33.22 vs. 551.97 ± 24.66 vs. 543.36 ± 37.74 µm, P < 0.001). Conclusions: Corneal stiffness is reduced in myopia and increased in hyperopia compared with emmetropia in children aged 4 to 6 years. Corneal biometry and biomechanical characteristics in preschool children seem to depend on refractive status.